SAT0121 Changes in Cytokine Profiles in Rheumatoid Arthritis Patients During Abatacept Treatment. (23rd January 2014) - Murakami, M.; Matsutani, T.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Namiki, M.; Ohmura, K.; Imura, Y.; Fujii, T.; Kuroiwa, T.; Nakahara, H.; Higa, S.; et al.
Abstract : Background: Dysregulated overproduction of cytokines is pathologically involved in the rheumatoid arthritis (RA). These cytokines include interferon (INF)-γ, interleukin (IL)-2, IL-4, IL-10, IL-6, IL-17, and tumor necrosis factor (TNF), etc. These cytokines are classified as T helper (Th)1, Th2 or Th17 cytokines. Abatacept (ABA), an inhibitor of CD28 co-stimulatory signaling, suppresses T cell activation, especially in Th populations. Objectives: This study aims to clarify changes of cytokine profiles in RA patients treated with ABA. Methods: Cytokine profiles were tested in 45 patients (anti-cyclic citrullinated peptide antibodies [ACPA] positive: 84.4%) enrolled in abatacept research outcome as a first-line biological agent in the real world (ABROAD study) at baseline and at 24 weeks of the ABA treatment. Fifteen healthy individuals (HIs) were also enrolled as controls. Plasma cytokines were measured with the BD Cytometric Bead Array Human Th1/Th2/Th17 kit (BD Bioscience, CA), and IL-17 were measured with the Quantikine® ELISA Human IL-17 kit (R&D Systems, Inc., Minneapolis, MN, USA). For the analysis of T cell subsets, cells were intracellularly stained with anti-IFN-γ, anti-IL-4 or anti-IL-17A antibodies after in vitro stimulation with PMA/Ionomycin. Results: Plasma levels of Th1 (IL-2 and IFNγ) and Th2 cytokines (IL-4 and IL-10) as well as the proportions of Th1 and Th2 cells were increased in some RA patients at baseline compared with HIs. While ABA treatment did not alter the proportions of Th1 and Th2 cells, their cytokine levels were decreased. Plasma levels of IL-6 at baseline were significantly higher in RA patients than in HIs (24.9±20.5 vs 7.1±4.0 pg/mL, P<0.001) regardless of the presence of ACPA. The plasma levels of IL-6 were significantly correlated with disease activity (CRP and MMP-3). ABA treatment for 24 weeks significantly reduced the plasma levels of IL-6 (24.9±20.5 vs. 11.5±7.7 pg/mL, P<0.001). Changes in IL-6 levels were also significantly correlated with the changes of CRP, DAS28-CRP and MMP-3. Proportion of Th17 cells was significantly decreased after ABA treatment while IL-17 levels did not changed. Conclusions: ABA treatment predominantly decreased IL-6 levels in association with the improvement of disease activity in RA patients. Disclosure of Interest: M. Murakami: None Declared, T. Matsutani Speakers bureau: Bristol-Myers Squibb Japan, M. Sekiguchi Grant/research support from: Bristol-Myers Squibb Japan, Speakers bureau: Bristol-Myers Squibb Japan, K. Matsui Grant/research support from: Bristol-Myers Squibb Japan, M. Kitano Grant/research support from: Bristol-Myers Squibb Japan, M. Namiki Grant/research support from: Bristol-Myers Squibb Japan, K. Ohmura Grant/research support from: Bristol-Myers Squibb Japan, Y. Imura Grant/research support from: Bristol-Myers Squibb Japan, T. Fujii Grant/research support from: Bristol-Myers Squibb Japan, T. Kuroiwa: None Declared, H. Nakahara: None Declared, S. Higa: None Declared, K. Maeda: None Declared, Y. Nozaki Grant/research support from: Bristol-Myers Squibb Japan, M. Funauchi Grant/research support from: Bristol-Myers Squibb Japan, K. Murakami: None Declared, T. Ikawa: None Declared, S. Irimajiri: None Declared, A. Nampei: None Declared, T. Azuma: None Declared, T. Sasaki: None Declared, A. Yokota: None Declared, S. Morita: None Declared, Y. Kawahito Grant/research support from: Bristol-Myers Squibb Japan, T. Mimori Grant/research support from: Bristol-Myers Squibb Japan, H. Sano Grant/research support from: Bristol-Myers Squibb Japan, N. Nishimoto Grant/research support from: Bristol-Myers Squibb Japan